Novel pituitary actions of GnRH in teleost: The link between reproduction and feeding regulation - Li, Wei; Du, Ruixin; Xia, Chuanhui; Zhang, Huiying; Xie, Yunyi; Gao, Xiaowen; Ouyang, Yu; Yin, Zhan; Hu, Guangfu (Frontiers in Endocrinology, 2022)
Gonadotropin-releasing hormone (GnRH), as a vital hypothalamic neuropeptide, was a key regulator for pituitary luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in the vertebrate. However, little is known about the other pituitary actions of GnRH in teleost. In the present study, two GnRH variants (namely GnRH2 and GnRH3) and four GnRH receptors (namely GnRHR1, GnRHR2, GnRHR3 and GnRHR4) had been isolated from grass carp. Tissue distribution displayed that GnRHR4 was more highly detected in the pituitary than the other three GnRHRs. Interestingly, ligand-receptor selectivity showed that GnRHR4 displayed a similar and high binding affinity for grass carp GnRH2 and GnRH3. Using primary culture grass carp pituitary cells as model, we found that both GnRH2 and GnRH3 could not only significantly induce pituitary reproductive hormone genes (GtHα, LHβ, FSHβ, INHBa, secretogranin-2) mRNA expression mediated by AC/PKA, PLC/IP3/PKC and Ca2+/CaM/CaMK-II pathways, but also reduce dopamine receptor 2 (DRD2) mRNA expression via Ca2+/CaM/CaMK-II pathway. Interestingly, GnRH2 and GnRH3 could also stimulate anorexigenic peptides (POMCb, CART2, UTS1, NMBa, and NMBb) mRNA expression via AC/PKA, PLC/IP3/PKC and Ca2+/CaM/CaMK-II pathways in grass carp pituitary cells. In addition, food intake could significantly induce brain GnRH2 mRNA expression. These results indicated that GnRH should be the coupling factor to integrate the feeding metabolism and reproduction in teleost.